2012
DOI: 10.3109/07420528.2012.682681
|View full text |Cite
|
Sign up to set email alerts
|

Role of Proinflammatory Cytokines on Lipopolysaccharide-Induced Phase Shifts in Locomotor Activity Circadian Rhythm

Abstract: We previously reported that early night peripheral bacterial lipopolysaccharide (LPS) injection produces phase delays in the circadian rhythm of locomotor activity in mice. We now assess the effects of proinflammatory cytokines on circadian physiology, including their role in LPS-induced phase shifts. First, we investigated whether differential systemic induction of classic proinflammatory cytokines could explain the time-specific behavioral effects of peripheral LPS. Induction levels for plasma interleukin (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…Moreover, interleukin-2 and TNF-alpha have been shown to alter sleep architecture in humans (Kapsimalis et al 2005;Opp 2005). The cytokine hypothesis might provide possible intervention targets for future drugs, since it has been already demonstrated that administration of soluble TNF-alpha receptor (soluble receptor binds to the cytokine and neutralizes it) prevents phase shift in locomotor activity in rats (Leone et al 2012;Paladino et al 2014). Translating these findings to human studies may alleviate circadian disruptions and the cluster of symptoms that often accompany patients with cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, interleukin-2 and TNF-alpha have been shown to alter sleep architecture in humans (Kapsimalis et al 2005;Opp 2005). The cytokine hypothesis might provide possible intervention targets for future drugs, since it has been already demonstrated that administration of soluble TNF-alpha receptor (soluble receptor binds to the cytokine and neutralizes it) prevents phase shift in locomotor activity in rats (Leone et al 2012;Paladino et al 2014). Translating these findings to human studies may alleviate circadian disruptions and the cluster of symptoms that often accompany patients with cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, activation of the immune system can also modulate the circadian clock. Peripheral LPS administration or introcerebroventricular (icv) injection of TNF-α or IL-1β produced phase delays in wheel running activity [17,39], and icv delivery of a proinflammatory cocktail also activated c-Fos expression in the SCN [40]. In addition, clock gene expression can be altered by exposure to different proinflammatory factors [41-44].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the sleep-wake cycle (partially controlled by the circadian clock) is modulated by immune factors, including TNF-α and IL-1β (10), and SCN physiology can be altered by infections that alter sleep architecture (11, 12). The presence of receptors for the proinflammatory cytokines TNF-α and IL-1β has been reported in the SCN (13, 14) and immune stimuli have been shown to modulate the phase of the master circadian clock (1517). Interestingly, the circadian response to a peripheral immune challenge is mediated by the action of TNF-α at the SCN level (15) suggesting an important role for this cytokine in immune-circadian communication.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of receptors for the proinflammatory cytokines TNF-α and IL-1β has been reported in the SCN (13, 14) and immune stimuli have been shown to modulate the phase of the master circadian clock (1517). Interestingly, the circadian response to a peripheral immune challenge is mediated by the action of TNF-α at the SCN level (15) suggesting an important role for this cytokine in immune-circadian communication.…”
Section: Introductionmentioning
confidence: 99%